2014
DOI: 10.1159/000360006
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Patterning of Host Innate Immune Responses by <b><i>Staphylococcus aureus</i></b> α-Toxin

Abstract: Immunomodulatory cytotoxins are prominent virulence factors produced by Staphylococcus aureus, a leading cause of bacterial sepsis, skin infection, and pneumonia. S. aureus α-toxin is a pore-forming toxin that utilizes a widely expressed receptor, ADAM10, to injure the host epithelium, endothelium, and immune cells. As each host tissue is characterized by a unique composition of resident cells and recruited immune cells, the outcome of α-toxin-mediated injury may depend on the infected tissue environment. Util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 46 publications
6
80
0
2
Order By: Relevance
“…Similarly, Hla elicits chemokine and cytokine release from host immune cells, epithelial cells, and endothelial cells (59)(60)(61)(62)(63)(64)(65), including the proinflammatory cytokine interleukin-1␤ (IL-1␤), an indicator of inflammasome activation and a major cytokine involved in the recruitment of neutrophils to the site of infection (66). Primary neutrophils display resistance to the lytic effects of Hla unless this toxin is present at high concentrations that would not likely be achieved early in the course of infection (65,67). Once recruited to the site of infection, host neutrophils would therefore either be subject to the lytic action of extracellular PSM peptides or sustain lysis from the intracellular compartment as engulfed bacteria produce PSMs (29).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hla elicits chemokine and cytokine release from host immune cells, epithelial cells, and endothelial cells (59)(60)(61)(62)(63)(64)(65), including the proinflammatory cytokine interleukin-1␤ (IL-1␤), an indicator of inflammasome activation and a major cytokine involved in the recruitment of neutrophils to the site of infection (66). Primary neutrophils display resistance to the lytic effects of Hla unless this toxin is present at high concentrations that would not likely be achieved early in the course of infection (65,67). Once recruited to the site of infection, host neutrophils would therefore either be subject to the lytic action of extracellular PSM peptides or sustain lysis from the intracellular compartment as engulfed bacteria produce PSMs (29).…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized MRSA strain Xen 30 (Xenogen/Caliper Life Sciences, Inc.), which was derived from S. aureus strain 16 and contains a luxABCDE operon in the chromosome, allowing for detection via bioluminescence in vivo (30). Although MRSA strains can vary in alphatoxin production (31)(32)(33), the virulence of the study strain was confirmed as equivalent to that of USA300 in the model as used in our prior studies (25). The virulence of strain Xen 30 was assessed in a previous study and demonstrated to be equivalent to that of other clinically relevant MRSA strains in the SSSI murine model (25).…”
Section: Methodsmentioning
confidence: 99%
“…Staphylococcal alpha-toxin (␣-hemolysin) is encoded by the hla gene, and the primary translation product functions as a precursor that is cleaved by signal peptidase and secreted into the extracellular medium (43). Association of the soluble, monomeric form of Hla with its ADAM10 host cell receptor triggers oligomerization and membrane pore formation (44), causing injury to vascular endothelial cells, epithelial cells, as well as platelets and cells of the myeloid lineage (45,46). During bloodstream infection of immunocompetent mice, the hla mutant of S. aureus Newman displayed reduced mortality and increased time to death (47).…”
Section: Resultsmentioning
confidence: 99%